A Proposed Algorithm for Encrypted Data Hiding in Video Stream Based on Frame Random Distribution - Hussien, Sura Abed Sarab; Hussien, Thair Abed Sarab; Noori, Mustafa Abdulsatar (Iraqi Journal of Science, 2021)
The science of information security has become a concern of many researchers, whose efforts are trying to come up with solutions and technologies that ensure the transfer of information in a more secure manner through the network, especially the Internet, without any penetration of that information, given the risk of digital data being sent between the two parties through an insecure channel. This paper includes two data protection techniques. The first technique is cryptography by using Menezes Vanstone elliptic curve ciphering system, which depends on public key technologies. Then, the encoded data is randomly included in the frame, depending on the seed used. The experimental results, using a PSNR within average of 65 and MSE within average of 85, indicate that the proposed method has proven successful in its ability to efficiently embedding data.